Preliminary observations on IGRA testing for TB infection in patients with severe COVID-19 eligible for immunosuppressive therapy - Torre, Alessandro; Aliberti, Stefano; Castellotti, Paola Francesca; Cirillo, Daniela Maria; Grisolia, Antonella; Mangioni, Davide; Marchetti, Giulia; Rossotti, Roberto; Santus, Pierachille; Besozzi, Giorgio; Villa, Simone; Codecasa, Luigi Ruffo (Respiratory medicine, 2020)
COVID-19, the novel coronavirus pandemic, has already spread around the globe affecting more than 18 million people. As previously observed with other coronaviruses, SARS-CoV-2 deeply dysregulate the immune system eliciting respiratory failure and a state of systemic hyperinflammation in severely ill individuals. Immunotherapy is often used to downgrade the detrimental effects of the disease sustained by high-level of cytokines. Those treatments, however, are known to undermine patients' ability to contain tuberculosis (TB) infection. This study aims to describe interferon-γ release assay (IGRA) results in severe COVID-19 patients eligible for immunosuppressive treatment. Aggregate data were gathered from five hospitals in Milan, Italy, from March 1 to May 15, 2020 and retrospectively analyses. Results were summarized using absolute frequencies and percentages and compared using a two-sided Chi-squared test. Overall, 462 COVID-19 patients were eligible for immunosuppressive therapy, among which 335 were tested using IGRA testing. More than one-third of them (122/335; 36.4%) had an indeterminate IGRA result because of insufficient immune response to mitogen control, 19 (5.7%) tested positive and 194 (57.9) negative. The majority of patients with lymphocytopenia (i.e., total lymphocyte count [TLC] below 1000 cells/mm ) had indeterminate IGRAs (81/155; 52.3%). The proportion becomes even higher in patients with severe lymphocytopenia (i.e., TLC<500 cells/mm ) (36/57; 63%). Our results suggest a possible negative impact of COVID-19 related immune dysregulation on TB infection assessment and management. Close monitoring of individuals with or without retesting of individuals with indeterminate IGRAs and further basic science investigations should to be sought to better comprehend their implication on TB epidemiology.